Postural adjustments of active youths in perturbation and dual-task conditions - Beretta, Victor Spiandor [UNESP]; Santos, Paulo Cezar Rocha [UNESP]; Jaimes, Diego Alejandro Rojas [UNESP]; Pestana, Mayara Borkowske [UNESP]; Jimenez, Alejandra Maria Franco [UNESP]; Scarabottolo, Catarina Covolo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (FapUNIFESP (SciELO), 2019)
Introduction: Cognitive components are necessary to maintain posture during external perturbations. However, few studies have investigated postural control when external perturbations are associated with a concomitant cognitive task (DT). Objectives: To analyze the behavior of reactive adjustments after perturbation with different intensities and displacements in active young adults; and to analyze the influence of DT on predictive and reactive adjustments in different perturbation conditions. Methods: Twenty-eight physically active young adults stood on an item of equipment that produced displacements of the base. Four experimental conditions were introduced in a single task (ST) and DT (cognitive-report how many times a pre-established number appeared in the audio): 1 (5 cm and 10 cm/s); 2 (5 cm and 25 cm/s); 3 (12 cm and 10 cm/s) and 4 (12 cm and 25 cm/s). Three attempts were carried out for each condition (total=24). Center of pressure (CoP) parameters were analyzed considering the following windows: predictive (-250 to +50 ms), reactive 1 (+50 to +200 ms) and reactive 2 (+200 to +700 ms), in comparison to the start of the CoP activity. One-way ANOVAs were performed to analyze predictive adjustments, while two-way ANOVAs with factor for task (STxDT) and condition (1x2x3x4), with repeated measurements, were performed for the reactive adjustments. Results: One-way ANOVA (predictive) indicated that the subjects had higher CoP parameters in ST vs DT. In reactive adjustments 1 and 2, ANOVA indicated greater CoP parameters in condition 2 and 4 when compared to 1 and 3, and in the ST vs DT. The subjects took longer to recover stable position in conditions 1 and 3 than in conditions 2 and 4. Conclusion: Perturbation intensity has a greater influence on postural adjustments to maintain balance than on magnitude. Moreover, the association of cognitive tasks with external perturbation decreases CoP oscillation. Therefore, cognitive resources play an important role in postural control after perturbation. Level of evidence III; Study of nonconsecutive patients, with no “gold” standard applied uniformly.
Ajustes posturales de jóvenes activos en condiciones de perturbación y doble tarea
Ajustes posturais de jovens ativos em condições de perturbação e tarefa dupla
Keywords: Cognition; Postural balance; Young adult